Pengaruh Kualitas Pelayanan, Nilai Yang Dirasakan, Pengalaman Pelanggan Terhadap Kepuasan Konsumen Pada PT Dinasty Han Djaya - Mir’atul Mukminah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Although PT Dinasty Han Djaya has generally demonstrated a high level of customer satisfaction, the company still faces a gap in achieving its internal customer satisfaction target due to weaknesses in supporting service aspects such as delivery speed and packaging conditions. Therefore, a more in-depth analysis is needed to examine the factors that influence customer satisfaction comprehensively. The objective of this research is to analyze the influence of service quality and perceived value, and customer experience on customer satisfaction at PT Dinasty Han Djaya in Bandar Lampung. A quantitative approach was employed in this research, and the data were collected through the administration of questionnaires to customers of PT Dinasty Han Djaya in Bandar Lampung. The research population comprises all clients who have used the services or products of PT Dinasty Han Djayaa who have used the products or services within the past three months. With 123 respondents as the sample, the study concludes that service quality, there are strong relationship between perceived value, customer perception, and customer satisfaction, both partially and simultaneously.